2020
DOI: 10.1002/smi.2931
|View full text |Cite
|
Sign up to set email alerts
|

Problem solving and affect as mechanisms linking daily mindfulness to task performance and job satisfaction

Abstract: This study investigated the daily relationships between mindfulness and job satisfaction via affect and mindfulness and task performance via problem solving confidence. Participants were 57 full‐time and part‐time employees who completed a baseline survey and five daily diary entries. Data were analysed using multilevel modelling. On days when they experienced greater mindfulness, employees also experienced (a) greater daily job satisfaction via high‐activation positive affect (but not low‐activation positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 65 publications
1
21
0
1
Order By: Relevance
“…As a personality trait, it is a characteristic that allows individuals to focus their attention on the present moment (Kabat Zinn, 2003) and prevent their thoughts from wandering (Real et al, 2017). Thus, attention and awareness are critical components of trait mindfulness (Forjan et al, 2020). Mindful people also exhibit high self-regulation, which makes them less likely to display autonomous behaviour (Glomb et al, 2011).…”
Section: Trait Mindfulnessmentioning
confidence: 99%
“…As a personality trait, it is a characteristic that allows individuals to focus their attention on the present moment (Kabat Zinn, 2003) and prevent their thoughts from wandering (Real et al, 2017). Thus, attention and awareness are critical components of trait mindfulness (Forjan et al, 2020). Mindful people also exhibit high self-regulation, which makes them less likely to display autonomous behaviour (Glomb et al, 2011).…”
Section: Trait Mindfulnessmentioning
confidence: 99%
“…Prior literature has found that those with high mindfulness and self-compassion are likely to be more satisfied with their jobs (Saini, 2020;Scarlet et al, 2017). Affect regulation suggests that those with high mindfulness are better able to regulate their emotions, and this can explain its relation with job satisfaction (Forjan et al, 2019). However, leaders with low mindfulness might struggle when dealing with interpersonal conflict, work-life balance and distress at work, which might reduce their overall job satisfaction (Raza et al, 2018;Scarlet et al, 2017).…”
Section: Note(s)mentioning
confidence: 99%
“…and selfcompassion (Forjan et al, 2019). Mindfulness interventions have also shown a positive relationship and indirect effect on well-being, job satisfaction and task performance among supervisors at work (Pang and Ruch, 2019) and health-care workers (Scarlet et al, 2017).…”
Section: Mindfulnessmentioning
confidence: 99%
“…Diverse mediators have been considered in the search to understand how mindfulness influences various organizational and employee well-being outcomes (see Shahbaz & Parker, 2021, for a review). Variables of interest have included vitality, sleep quality (Allen & Kiburz, 2012); surface acting (Hülsheger et al, 2013); authentic functioning (Leroy et al, 2013); self-regulatory focus (Zivnuska et al, 2017); future focus, state arousal, detachment (Hafenbrack & Vohs, 2018); high-activation positive affect, problem-solving confidence (Forjan et al, 2020); and cognitive reappraisal (Kay & Skarlicki, 2020). Though the body of literature is small, these illustrative examples already highlight the diverse range of mediating factors of potential relevance in the work context.…”
Section: Mechanisms Of Mindfulnessmentioning
confidence: 99%